21 Can conisation specimens predict sentinel lymph node status in early-stage cervical cancer? A senticol group study. (13th November 2020) - Mereaux, J; Balaya, V; Guani, B; Magaud, L; Bonsang-kitzis, H; Ngô, C; Lecuru, F; Mathevet, P
Abstract : Objectives: The goal of this study was to determine pathologic risk-factors on conisation specimen predicting the sentinel lymph node (SLN) in early-stage cervical cancer. Methods: An ancillary analysis of 2 prospective multicentric database on SLN biopsy for cervical cancer (SENTICOL I and II) were carried out. Patients with IA to IB1 FIGO stage, who underwent SLN biopsy and conisation were included. Results and Discussion: Between January 2005 and July 2012, 161 patients from 25 French centers fulfilled the inclusion criteria. The majority of patients had IB1 clinical FIGO stage (81.4%) and squamous cell carcinoma (76.3%). Macrometastases, micrometastases and Isolated tumor cells (ITCs) were found in 4 (2.5%), 6 (3.7%) and 5 (3.1%) patients respectively. Compared to negative SLN patients, patients with micrometastases or macrometastases were more likely to have lymphovascular space invasion (LVSI) (60% vs 29.5%, p = 0.04) and deep stromal invasion (DSI) ≥ 10 mm (50% vs 17.8%, p = 0.046). By multivariate analysis, DSI ≥ 10 mm on conisation specimens was an independent factor of micrometastases and macrometastases (OR = 3.91, 95%CI = [ 1.03 – 14.9], p = 0.046). Among the 94 patients with DSI < 10 mm and absence of LVSI on conisation specimens, 4 patients (4.2%) had ITCs and only one (1.1%) had micrometastases. Conclusions: Patients with DSI ≥ 10 mm and LVSI had higher risk of micrometastatic and macrometastatic SLN. In this subpopulation, SLN mapping should be performed meticulously to avoid missing metastatic nodes.